Efficacy of intravenous high-dose methotrexate in preventing relapse to the central nervous system in R-CHOP(-like)-treated, high-risk, diffuse large B-cell lymphoma patients and its effect on mortality: a systematic review and meta-analysis - Elisabeth R. Tolley; Christian Lewinter; Lars M. Pedersen; Torsten Holm Nielsen (Haematologica, 2024)
CNS relapse in patients with diffuse large B-cell lymphoma (DLBCL) carries a dismal prognosis with most clinical guidelines recommending CNS prophylaxis to patients deemed at high risk for CNS relapse. However, results from observational studies investigating the effect of CNS prophylaxis have yielded conflicting results. Objectives: To evaluate: 1) whether addition of prophylactic intravenous HD-MTX reduces the risk of CNS relapse in high-risk DLBCL patients treated with R-CHOP or similar and 2) whether HD-MTX prophylaxis confers an overall survival benefit, irrespective of CNS relapse. Methods: A systematic search of MEDLINE/PubMed and EMBASE on DLBCL patients at high risk of CNS relapse treated with R-CHOP or similar receiving HD-MTX as intervention and a comparator arm receiving no prophylaxis and/or IT prophylaxis. Risk of Bias was estimated using the ROBINS-I tool and the quality of the evidence by the GRADE approach. Finally, a meta-analysis based on the systematic review was conducted. Results: A total of 1812 studies were screened. No RCT’s were identified. Seven observational studies comprising 1661 patients met inclusion criteria. We found a statistically non-significant relative risk of 0.54 [0.27-1.07, 95% CI] of CNS relapse for patients receiving HD-MTX vs. controls. The meta-analysis investigating mortality demonstrated a relative risk of death of 0.70 [0.44-1.11, 95% CI] for HD-MTX treated vs. controls. The overall risk of bias was adjudged as “serious” and the quality of the evidence was rated as low. Conclusion: Our data indicate that HD-MTX does not prevent, or at best, only slightly reduces the risk of CNS relapse and confers no survival benefit.